Metabolic dysfunction-associated fatty liver disease and risk of nephrolithiasis: a sizeable cross-sectional study - Zheng, Shengqi; Hua, Tianchi; Yin, Guicao; Zhang, Wei; Wang, Xiaoxiang; Qi, Lezhong; Jing, Xiayong; Fan, Qibing; Yu, Xiaoping; Li, Yifan (Frontiers in Endocrinology, 2025)
ObjectiveMetabolic dysfunction-associated fatty liver disease (MAFLD) and nephrolithiasis are two common metabolic diseases, but their relationship has not yet been thoroughly studied. Therefore, this study aimed to explore the association between MAFLD and nephrolithiasis and to assess the effect of MAFLD on the risk of nephrolithiasis.Materials and methodsThis cross-sectional study included 96,767 adults from China. All participants underwent medical examinations, including physical examinations, medical history tests, and laboratory tests. Based on ultrasound examination, participants were divided into MAFLD and non-MAFLD groups, and the severity of liver steatosis was determined based on ultrasound images. The relationship between MAFLD and nephrolithiasis was analyzed using a multivariate logistic regression model and subgroup analysis was performed.ResultsThe proportion of participants with MAFLD was significantly higher in the nephrolithiasis group compared to the non-nephrolithiasis group (47.70% vs. 30.45%, P < 0.001). Multivariate logistic regression analysis showed a significant positive association between MAFLD and nephrolithiasis (adjusted OR=1.38, 95% CI: 1.29 to 1.47). Subgroup analyses indicated that, even after accounting for various factors such as age, diabetes, hypertension, obesity, lipid profiles, and renal function, the positive association between MAFLD and an increased risk of nephrolithiasis remained consistent. Further subgroup analysis revealed that in male patients with MAFLD, the risk of nephrolithiasis increased progressively with increasing severity of liver steatosis. The adjusted multivariable odds ratios were 1.43 (95% CI: 1.33 to 1.53) for mild, 1.48 (95% CI: 1.32 to 1.67) for moderate, and 1.94 (95% CI: 1.47 to 2.58) for severe hepatic steatosis.ConclusionsThis study found a significant positive association between MAFLD and nephrolithiasis. The risk of nephrolithiasis in males with MAFLD increased substantially with increasing severity of liver steatosis. Therefore, it is essential to strengthen prevention and screening for nephrolithiasis in individuals with MAFLD. More research is needed to elucidate the physiological and pathological mechanisms between MAFLD and nephrolithiasis.